Skills Improvement of Villagers Tambakrejo District Gurah Via Herbal Product Manufacturing Training - Dona Wahyuning Laily; Dita Atasa; Prasmita Dian Wijayanti; Ida Syamsu Roidah (Future Science, 2022)
The outputs of this activity include the first, namely: improve the knowledge, skills and motivation of the target partners in particular women from RT 01 RW 02 Tambakrejo Village in utilizing herbal plants used for the manufacture of herbal drink products. Second is to make preparations for making simple herbal products and their maintenance can be implemented by the government. There are several steps that will be carried out to achieve the output targets, namely: (1) the first meeting explained the material about utilization of herbal plant planting and nursery training, (2) meeting the second is making various kinds of herbal drinks, and (3) the third meeting is effective marketing that may be used to increase income in society. The results of the activities that have been carried out are: can provide knowledge about the manufacture of herbal products in the form of drinks taken from the herbal plant. Service empowerment program This community is expected to be able to assist target partners in evaluating problems and increase the productivity of target partners.